Key performance indicators (KPls) for governance of public universities in Malaysia. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2006)
The National Higher Education academic groups of Public Research Institute (IPPTN) together with the Asian Centre of Research (PIHL) in Malaysia and the on University Learning and preparation of the instrument Teaching (ACRULcT), Univcrsiti process. Teknologi MARA, organised a workshop on "Key Performance Indicators (KPls) for Governance of Public Universities in Malaysia" from 28 to 31 May 2006, at the Grand Plaza Parkroyal Hote l, Penang